KINERJA KEUANGAN ASURANSI SYARIAH DI INDONESIA - Wahyudi, Nico; Hariyani, Diyah Santi; Ubaidillah, Moh. (JEB17 : Jurnal Ekonomi dan Bisnis, 2020)
This study aims to assess the financial performance of Sharia Insurance companies in Indonesia in the period 2017-2019 using risk-based capital (RBC) and Early Warning System (EWS) financial ratios. This research data uses secondary data accessed from the financial statements of Sharia Insurance companies registered with the Financial Services Authority (OJK) during the period 2017-2019. Qualitative descriptive data analysis techniques. Based on the management of analysis data using ratios, it can be known the performance condition of insurance companies registered with the Financial Services Authority from 2017 to 2019 as many as seven companies can be categorized in good condition while five companies are categorized as bad based on the provisions of PSAK No. 28.